The Influence of Sustainability, Non-Performing Financing, and Capital Structure on Firm Value: Mediated by Financial Performance - Oktaviani, Delvi; Kurniasih, Augustina (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This research aims to examine the impact of Sustainability Report Disclosure (SRD), Non-Performing Financing (NPF), and Capital Structure on Firm Value, with Financial Performance acting as an intervening variable, in multifinance companies. The study focuses on multifinance companies listed on the Indonesia Stock Exchange (IDX) during the 2024 period. The sample consists of multifinance companies listed on the IDX from 2020 to 2023 that consistently publish annual sustainability reports. The results indicate that SRD has insignificant positive effect on firm value, while it has significant positive effect on financial performance. NPF has a significant negative effect on firm value but an insignificant negative effect on financial performance. DER has a significant negative effect on firm value but an insignificant positive effect on ROA. Furthermore, ROA does not mediate the impact of SRD, NPF, and DER on firm value.